(untitled) (Ciudades, 2018)
The retail activities in Spain have changed in the last thirty years. The relations with public places and public transport have changed too. The city fragments itself. It specializes its activities and places. Great stores located in outskirts districts take place in this framework of sprawled city. The Eighties were a transition period. Warehouses were opened in district centres of Madrid, simultaneously retail parks were inaugurated in outlying districts. In the Nineties, a lot of suburb superstores and retail parks were opened. At the beginning of this century, retail parks are authentic territorial nodes in the urban area of Madrid. The retail parks locations create a new hierarchy for the urban centres of this city. The Spanish average in this type of retail triples to the European average. The new retail generates a great impact in the traditional retail, as well as in the vitality of the urban public spaces.